Clostridium difficile infection after ileostomy closure and anastomotic failure in rectal cancer surgery patients. Issue 2 (21st April 2022) - Kim, Young Il; Yu, Chang Sik; Kim, Yang Soo; Kim, Chan Wook; Lee, Jong Lyul; Yoon, Yong Sik; Park, In Ja; Lim, Seok-Byung; Kim, Jin Cheon
Abstract: Background: Diverting ileostomy during resection of rectal cancer is frequently performed in patients at risk of anastomotic failure. Clostridium difficile infection (CDI) is reported to be frequent in patients who receive ileostomy closure with a questionable association to postoperative anastomosis leak. The primary aim of this study was to determine the incidence of CDI following ileostomy closure in patients who underwent rectal cancer surgery; the secondary aim was to assess the rate of postileostomy closure CDI in patients who presented with leakage at the original colorectal anastomosis site. Methods: Medical records of patients with rectal cancer who underwent ileostomy closure between January 2015 and December 2019 were retrospectively reviewed. All patients had previously received resection and anastomosis for primary rectal cancer with diverting ileostomy. Data regarding CDI incidence, preoperative status, perioperative management, and clinical outcomes were collected. CDI positivity was determined by direct real-time PCR and enzyme-linked fluorescent assays for detecting toxin A and B.Statistical analyses were computed for CDI risk factors. Results: A total of 1270 patients were included and 208 patients were tested for CDI owing to colitis-related symptoms. The incidence of CDI was 3.6 per cent (46 patients). Multivariable analysis for CDI risk factors identified adjuvant chemotherapy (hazard ratio (HR) 2.28; P = 0.034) and colorectal anastomosis leakage prior to CDI (HR 3.75; P = 0.008). Finally, patients with CDI showed higher colorectal anastomosis leakage risk in multivariable analysis after ileostomy closure (HR 6.922; P = 0.001). Conclusion: Patients with CDI presented with a significantly higher rate of colorectal anastomosis leakage prior to ileostomy closure. Abstract : Adjuvant chemotherapy and colorectal anastomosis leakage increase risk of Clostridium difficile infection. Patients with Clostridium difficile infection also have a higher risk of anastomosis leakage after rectal surgery.